Relationship Between Single-Leg Vertical Jump and Drop Jump Performance, and Return to Sports After Primary Anterior Cruciate Ligament Reconstruction Using Hamstring Graft - Shunsuke Ohji; Junya Aizawa; Kenji Hirohata; Takehiro Ohmi; Tomoko Kawasaki; Hideyuki Koga; Kazuyoshi Yagishita (International Journal of Sports Physical Therapy)
# Background